2009
DOI: 10.1002/mnfr.200800600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L‐asparaginase on acrylamide mitigation in a fried‐dough pastry model

Abstract: A dough resembling traditional Spanish rosquillas was used as a model to represent classical fried‐dough pastry to investigate the effects of asparaginase and heat treatment on amino acid levels and acrylamide mitigation. Wheat‐based dough was deep fried at 180 and 200°C for 4, 6, and 8 min. Two recipes were formulated by addition of different asparaginase levels (100 and 500 U/kg flour) to the dough. The temperature/time profile of the frying process, moisture, sugars, amino acids, acrylamide, and some indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 26 publications
1
31
1
4
Order By: Relevance
“…In addition, lipid-derived carbonyl compounds can react with amino groups leading to increased rate of browning (Arnoldi, Arnoldi, Baldi, & Griffini, 1987). Addition of the enzyme did not affect the color (P N 0.05), in agreement with literature data (Capuano et al, 2009;Kukurová et al, 2009). Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, lipid-derived carbonyl compounds can react with amino groups leading to increased rate of browning (Arnoldi, Arnoldi, Baldi, & Griffini, 1987). Addition of the enzyme did not affect the color (P N 0.05), in agreement with literature data (Capuano et al, 2009;Kukurová et al, 2009). Fig.…”
Section: Resultssupporting
confidence: 91%
“…This is the reason why the enzyme was more effective when added in the aqueous phase of the dough preparation instead of in the mixture (Amrein et al, 2004). Furthermore, acrylamide levels due to asparaginase incorporated to model systems were higher (85% to 90% as respect to a reference) than those reported for biscuits (27% to 70% as respect to a reference) (Anese, Quarta, & Frias, 2011;Capuano et al, 2009;Ciesarová et al, 2006;Hendriksen et al, 2009;Kukurová et al, 2009;Zyzak et al, 2003). These differences in asparaginase efficacy could be due to the different complexity from the compositional standpoint of the systems considered.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…By adding l-asparaginase before food baking or frying, l-asparagine can be biologically converted into l-aspartic acid, which does not participate in the formation of acrylamide, and thus the formation of acrylamide can be significantly reduced ). In the previous works, l-asparaginase treatment has been demonstrated to have a significant effect on the acrylamide mitigation in cereal-and potato-based foods (Kumar et al 2014a;Anese et al 2011;Kukurova et al 2009;Hendriksen et al 2009;Pedreschi et al 2008). And currently, l-asparaginases from Aspergillus niger (Koster 2007) and Aspergillus oryzae ) have been commercially used for the purpose of reducing acrylamide formation.…”
Section: Introductionmentioning
confidence: 95%
“…A number of strategies have been proposed to control acrylamide levels in food products, such as choosing food materials containing smaller amounts of precursors for acrylamide formation, i.e., reducing sugars and asparagine (Amrein et al, 2003;Rommens et al, 2008); removing the above-mentioned precursors (Baardseth et al, 2006;Kukurová et al, 2009); processing food materials under conditions that suppress the formation of acrylamide, i.e., at low temperatures (Granda et al, 2004); and adding food ingredients capable of inhibiting the formation of acrylamide (Zheng et al, 2009;Cheng et al, 2010). It was also reported that the addition of certain amino acids other than asparagine reduces acrylamide levels in an aqueous system (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%